STUDIES ON PHENOLASE ENZYME IN PRAWNS II THE INHIBITORY ACTION ON THE ENZYME BY CERTAIN CHEMICAL AGENTS. - ANTONY, P D; NAIR, M R (Fishery Technology, 2017)
The effect of certain chemical agents on dopa oxidation by phenolases has been examined. Sulphur containing amino carboxylic acids are inhibitory agents for dopa oxidation. Tyrosine, a substrate for the enzyme also acts as an inhibitor for dopa oxidation by the enzyme. The possible mode of action has been discussed. The function of diethyl dithiocarbamate in suppressing the display of enzyme activity has been detailed and its behaviour has been compared to the other chemical agents studied.